2021
DOI: 10.1097/ppo.0000000000000540
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Response in Glioblastoma

Abstract: Glioblastoma (GBM) is an intrinsically treatment-resistant tumor and has been shown to upregulate DNA damage response (DDR) components after treatment. DNA damage response signaling mediates treatment resistance by promoting cell cycle arrest in order to allow for DNA damage repair and avoid mitotic catastrophe. Therefore, targeting the DDR pathway is an attractive strategy to combat treatment resistance in GBM. In this review, we discuss the different DDR pathways and then summarize the current preclinical ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 67 publications
(125 reference statements)
0
5
0
Order By: Relevance
“…Tumor cells can also repair their own DNA through the above pathway to avoid apoptosis and increase invasiveness. Previous studies have found that glioblastoma contains stem cell-like subsets, showing high expression of DNA damage response factors, resulting in therapeutic resistance and disease recurrence [ 39 ].At present, the clinical trials of DDR inhibitors in gliomas are very popular, and the therapeutic targets include:PARP/ DNA-PK/Chk1/ATM [ 40 ]. However, there is no targeted drugs with clear benefits have been found so far, we speculate that it may be because the specific DDR pathway inhibitors were not selected for treatment based on the corresponding high expression biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells can also repair their own DNA through the above pathway to avoid apoptosis and increase invasiveness. Previous studies have found that glioblastoma contains stem cell-like subsets, showing high expression of DNA damage response factors, resulting in therapeutic resistance and disease recurrence [ 39 ].At present, the clinical trials of DDR inhibitors in gliomas are very popular, and the therapeutic targets include:PARP/ DNA-PK/Chk1/ATM [ 40 ]. However, there is no targeted drugs with clear benefits have been found so far, we speculate that it may be because the specific DDR pathway inhibitors were not selected for treatment based on the corresponding high expression biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Intact p53 activity is required for efficient cell cycle progression through the G1/S checkpoint, its mutational loss of function is allowing cancer cells to pass the checkpoints with replicating errors and to accumulate DNA damage (Ref. 16). For example, treatment with RT and DNA-PK inhibitor M3814 on p53 mutated cell lines lead to mitotic catastrophe and apoptotic cell death, as the replication mechanism was unable to arrest the cell cycle and repair the induced DNA damage (Ref.…”
Section: Biomarkers Of Ddr Pathway Statusmentioning
confidence: 99%
“…Thus, there are some limitations regarding the treatment with ATR inhibitors, as they could harm both cancerous and noncancerous cells. At the moment, there are no specific ATR inhibitors clinical trials for GBM, due to their increased toxicity in preclinical studies (Refs 16, 95). Yet, there are ongoing clinical trials that test ATR inhibitors in combination with RT or other chemotherapy: Elimusertib (BAY1895344) with Pembrolizumab for advanced solid tumours (NCT04095273) or Elimusertib with Pembrolizumab and Stereotactic Body Radiation Therapy for recurrent head and neck cancer (NCT04576091) or AZD6738 with Olaparib (AZD2281) for Clear Cell Renal Cell Carcinoma and Advanced Pancreatic Cancer (NCT03682289).…”
Section: Current Therapeutic Approaches Targeting Ddr In Gbmmentioning
confidence: 99%
See 2 more Smart Citations